The Effect Of Self-Efficacy, Training And Competence On Employee Performance With Work Motivation As A Mediator (Empirical Study on Telecom System Sub-Sector Companies) - Rorenso Rakhitta Damma Setiawan (LPPM Universitas Buddhi Dharma, 2026)
This study aims to analyze the influence of self-efficacy, training, and competence on employee performance with work motivation as a mediating variable in a sub-telecom system company. Self-efficacy is an individual's belief in their ability to complete tasks and face challenges at work. Training plays an important role in improving employee skills and knowledge in order to be able to keep up with industrial developments, especially in the telecommunications system sector which is experiencing rapid technological changes. Competence is the main factor in determining the extent to which an employee has the skills, knowledge, and work attitudes that are in accordance with company standards. Work motivation acts as a drive for employees to improve their performance, which is influenced by external and internal factors. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis method. Respondents in this study were employees who worked in a telecommunications system company. The results of this study indicate that Training, Competence and Work Motivation have an influence on employee performance. Meanwhile, Self-Efficacy has no influence on Employee Performance. Self-Efficacy, Training have an influence on Work Motivation and Competence has no influence.